The Role of Language Editors in Improving the Quality of Academic Books Published By University Presses - Setiawan, B; Saddhono, K; ., Purwadi (KnE Social Sciences, 2018)
The purpose of this research is to improve the role of language editors in university press management, particularly in Indonesia, in publishing universities’ intellectual assets. The method used was a descriptive qualitative design by focusing on group discussions, seminars, workshops, and training. The results showed that the university press was the most important pillar in the implementation of Tri Dharma University and had a vital role in publishing and distributing the intellectual assets of higher education to the public. Good management will ultimately create a professional university press. Aspects such as editorial management were considered, particularly in language editing, because of the essential role of connecting writers’ ideas to the readers. There have been some experiences in Indonesia where the University Press proved that a well-managed publishing will produce a positive impact to the university. The academic sphere will apparently appear in every activity related to publication and will present a positive image toward universities. Keywords: academic book, language editors, university press management